K(ATP) channels and cardiovascular disease: Suddenly a syndrome - Nichols, Colin G. (2013)
ATP-sensitive potassium (K(ATP) ) channels were first discovered in the heart 30 years ago(1). Reconstitution of K(ATP) channel activity by coexpression of members of the pore-forming inward rectifier gene family (Kir6.1, KCNJ8, and Kir6.2 KCNJ11) with sulfonylurea receptors (SUR1, ABCC8, and SUR2, ABCC9) of the ABCC protein sub-family, has led to the elucidation of many details of channel gating and pore properties. In addition, the essential roles of Kir6.x and SURx subunits in generating cardiac and vascular K(ATP)(2) and the detrimental consequences of genetic deletions or mutations in mice have been recognised(3). However, despite this extensive body of knowledge, there has been a paucity of defined roles of K(ATP) subunits in human cardiovascular diseases, although there are reports of association of a single Kir6.1 variant with the J-wave syndrome in the electrocardiogram, and two isolated studies have reported association of loss of function mutations in SUR2 with atrial fibrillation and heart failure. Two new studies convincingly demonstrate that mutations in the SUR2 gene are associated with Cantu syndrome, a complex multi-organ disorder characterized by hypertrichosis, craniofacial dysmorphology, osteochondrodysplasia, patent ductus arteriosus, cardiomegaly, pericardial effusion, and lymphoedema. As we discuss, this realization of previously unconsidered consequences provides significant insight into the roles of the K(ATP) channel in the cardiovascular system and suggests novel therapeutic possibilities.